Performance, Carcass Traits, and Meat Composition of Broiler Chickens Fed Diet Containing Fish Oil and Vitamin E - Sumiati; A. Darmawan; W. Hermana (Tropical Animal Science Journal, 2022)
The study aimed to determine the efficacy of dietary vitamin E and fish oils on performance, carcass yield, cholesterol, omega-3, and omega-6 in the meats of broiler chickens. A total of 400 Lohmann day-old broiler chicks consisted of 200 males and 200 females were reared for 35 days. This experiment employed a completely randomized design with five treatments and four replicates. The treatments were T0: Control diet with 3% crude palm oil without vitamin E; T1: Diet containing 3% fish oil; T2: Diet containing 3% fish oil and 80 IU/kg vitamin E; T3: Diet containing 3% fish oil and 100 IU/kg vitamin E, and T4: Diet containing 3% fish oil and 120 IU/kg vitamin E. The result showed that dietary fish oil and vitamin E had no effect (p>0.05) on feed intake, body weight, weight gain, AME, AMEn, TME, and TMEn, but it tended to decrease the mortality rate. T3 significantly reduced (p<0.05) FCR in the finisher phase and meat cholesterol compared to the control. T1 and T3 significantly (p<0.05) reduced carcass weight percentage. Dietary fish oil and vitamin E increased omega-3 levels, and declined the ratio of omega-6 and omega-3. It is concluded that supplementation of 100 IU Vitamin E in the diet containing 3% fish oil improved feed efficiency by 9.95%, decreased cholesterol of the meat by 44.76%, increased omega-3 of the meat by 81.92%, and yielded the best ratio of omega-6: omega-3 of the meat, i.e., 10.34:1.